Optimal Planning of Electric Vehicles Energy Exchange in Parking Lots Considering Uncertainties - Sanchez, David A.; Torres, Santiago P.; Chillogalli, Jose E.; Chamorro, Harold R.; Gonzalez, Luis G.; Sood, Vijay K.; Romero, Ruben R. [UNESP] (Institute of Electrical and Electronics Engineers (IEEE), 2022)
With the growing concern for energy conservation and environmental protection around the world, the use of Electric Vehicles (EVs) is being encouraged. In this way, the optimum allocation of EVs' parked in a distribution network is a challenging issue. In this paper, the optimal energy exchange between EVs and the distribution network is analyzed in two types of parking lots, which will be controlled by a charging provider or aggregator, and where the randomness related to vehicles and vehicle-to-grid (V2G) capability at the charging stations will be considered. In this way the stochastic behavior of an EV during the day was formulated as a mixed integer linear programming (MILP) problem, and Monte Carlo simulations were used to estimate the optimal loading and unloading patterns of EVs inside the parking lots based on the time-of-use (ToU) tariffs.
Keywords: Electric Vehicles; Monte Carlo simulation; optimization energy Exchange; time-of-use tariffs